Analysis of the Implementation of Policies for Handling Emergency Covid 19 Infectious Diseases at Royal Prima Hospital Medan 2020 - Heny; Mangatas Silaen; Tan Suyono; Adhayani (CV. Inara, 2022)
This study aims to analyze the implementation of the policy for handling the infectious disease covid 19 at the Royal Prima Medan Hospital in 2020. The sample in this study amounted to 69 people. All data is obtained by analysis so that the data can provide useful meaning to solve research problems. We use univariate Analysis, bivariate analysis, and multivariate analysis. The research result shows that there is no relationship between policies and commitments with handling Covid, there is a relationship between planning and handling Covid, there is no relationship between organizing and handling Covid, and there is a relationship between implementation and handling Covid. We hope that the hospital will support and carry out the implementation of the policy for handling the infectious disease covid 19 at Royal Prima Hospital for the sake of high-quality service results. Future researchers are expected to examine more sources and references related to the analysis of the implementation of the Covid 19 so that the research results can be better and more complete.